Rapid Diagnosis of Malaria - Clinton K. Murray; Jason W. Bennett (Interdisciplinary Perspectives on Infectious Diseases)
Malaria's global impact is expansive and includes the extremes of the healthcare system ranging from international travelers returning to nonendemic regions with tertiary referral medical care to residents in hyperendemic regions without access to medical care. Implementation of prompt and accurate diagnosis is needed to curb the expanding global impact of malaria associated with ever-increasing antimalarial drug resistance. Traditionally, malaria is diagnosed using clinical criteria and/or light microscopy even though both strategies are clearly inadequate in many healthcare settings. Hand held immunochromatographic rapid diagnostic tests (RDTs) have been recognized as an ideal alternative method for diagnosing malaria. Numerous malaria RDTs have been developed and are widely available; however, an assortment of issues related to these products have become apparent. This review provides a summary of RDT including effectiveness and strategies to select the ideal RDT in varying healthcare settings.